Is stress related to itch in German students? Results of an online survey - Kiupel, Stephanie; Kupfer, Jörg; Kottlors, Sophia; Gieler, Uwe; Yosipovitch, Gil; Schut, Christina (Frontiers in Medicine, 2023)
German students report to be more stressed than the general population. Highly stressed students from other countries (US, Australia, Saudi-Arabia) were found to have more skin symptoms, including itch, than lowly stressed students. The current study aimed to assess whether itch is associated with stress in a larger sample of German students. 838 students (3.2 % of all invited students) took part in the questionnaire based study and filled in the Perceived Stress Questionnaire as well as a modified version of the Self-Reported Skin Questionnaire. Students were categorized into highly (HSS) and lowly stressed students (LSS) by determination of the 25th and 75th percentile. Itch occurred significantly more often in HSS compared to LSS (OR = 3.41 (2.17 - 5.35)). In addition, itch intensity was significantly related to perceived stress. These findings not only highlight the importance of offering stress management trainings also to students in Germany in order to minimize itch, but also encourage future research on stress and itch in certain student subgroups.